(-7v-6)-(2v-4)=

Simple and best practice solution for (-7v-6)-(2v-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-7v-6)-(2v-4)= equation:


Simplifying
(-7v + -6) + -1(2v + -4) = 0

Reorder the terms:
(-6 + -7v) + -1(2v + -4) = 0

Remove parenthesis around (-6 + -7v)
-6 + -7v + -1(2v + -4) = 0

Reorder the terms:
-6 + -7v + -1(-4 + 2v) = 0
-6 + -7v + (-4 * -1 + 2v * -1) = 0
-6 + -7v + (4 + -2v) = 0

Reorder the terms:
-6 + 4 + -7v + -2v = 0

Combine like terms: -6 + 4 = -2
-2 + -7v + -2v = 0

Combine like terms: -7v + -2v = -9v
-2 + -9v = 0

Solving
-2 + -9v = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -9v = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -9v = 0 + 2
-9v = 0 + 2

Combine like terms: 0 + 2 = 2
-9v = 2

Divide each side by '-9'.
v = -0.2222222222

Simplifying
v = -0.2222222222

See similar equations:

| 6(2+15x)= | | 2/7-1/14 | | 32b-4+-2b-1= | | 10+5r=10-r | | (2/x)-x=(-23/5) | | (7/8)/m=(1/7) | | =(2a+3b-4c) | | 4+5-2=33 | | -2y+6+9y= | | 2/3-1/x=5/3x | | 3(n-4)=-15 | | X*.38=112 | | 26x^2-130x+6=0 | | 4x^2-y^2=11 | | 14j+3k= | | X^2+x+1=2 | | 8x+2z=4+7y | | 5x+2.5y=840 | | 7p-10=-3p+5 | | 10p+5=5p-5 | | 12y+8=13y-18 | | 20-2x=x+8 | | x^2-10=350 | | 17=9y-5y-3 | | yl=14j+3k | | 11=-9x+5x | | 324÷1/8 | | 16N=2(N+12)+2N | | 5x+5=6y | | 7(x-9)=14 | | 2x+(5x-3y)= | | 16N=(N+12)+2N |

Equations solver categories